Typical investigative situations for medical criminal offenses - Seidanov, A.B.; Kumisbekov, S.K. (Bulletin of the Karaganda University “Law Series”, 2022)
The article attempts to characterize one of the structural elements included in the content of the methodology of pre-trial investigation of criminal offenses — typical investigative situations formed during pre-trial pro-ceedings on medical criminal offenses. The analysis of the state of investigation of medical criminal offenses according to statistical information throughout the Republic was carried out, wishes were expressed for de-tailing statistical data in two positions. To improve the efficiency of the investigation and inquiry units during pretrial proceedings on medical criminal offenses, typical investigative situations arising at the beginning of a pre-trial investigation for this group of criminal offenses are proposed. Each typical investigative situation is described with its characteristic features, favorable and unfavorable sides are indicated. The available ca-pabilities of modern criminology make it possible to develop the professionalism of investigative units and bodies of inquiry in the fight against crime during the pre-trial investigation of criminal cases, which must be implemented through the prevailing typical investigative situations, including an approximate algorithm for pre-trial investigation of medical criminal offenses.